Tyrictaca hyalina (Kallies & Arita, 2001) (Lepidoptera: Sesiidae: Tinthiini)—a description of pupa and the introduction into Europe on an infested Ficus microcarpa - Bąkowski, Marek; Gruszka, Anna; Larysz, Adam (Zootaxa, 2021)
The clearwing moth, Tyrictaca hyalina (Kallies & Arita, 2001) (Tinthiini, Sesiidae), was reared from cultivated Ficus microcarpa L.f. which were imported from China to Poland. Tyrictaca hyalina is native to southeast Asia and was probably reared before from the same imported Ficus plants in Germany and France. This article presents the first description of the pupal morphology of Tyrictaca. We compare the description of pupal morphology of T. hyalina to known morphological features of the pupae of other Tinthiini species. The morphological characters of adult and male genitalia are also presented.